Evolutionary multi-objective Pareto optimisation of diagnostic state observers - Kowalczuk, Zdzisław; Suchomski, Piotr; Białaszewski, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
A multi-objective Pareto-optimisation procedure for the design of residual generators which constitute a primary instrument for model-based fault detection and isolation (FDI) in systems of plant monitoring and control is considered. An evolutionary approach to the underlying multi-objective optimisation problem is utilised. The resulting robust observer detector allows for FDI, taking into account the issue of false alarms.
Keywords: diagnostics; fault detection and isolation; genetic algorithms; multiobjective optimisation; Pareto-optimality; residuals; state observers